Measuring Awareness of Over the Counter Analgesics Use and Risks Associated With it Among Jordanian Population in Amman - AL-Samydai, Ali; Al-Elaime, Lena A.; Abbadi, Sundos H.; Khareisha, Lubna Al- (Asian Journal of Pharmaceutical Research and Development, 2018)
This is an observational cross-sectional study that examines the awareness of Jordanian consumers regarding the potential risks associated with over-the-counter (OTC) use of paracetamol and non-steroidal anti-inﬂammatory drugs (NSAIDs) and the effect of family and friends’ advice on the use of analgesics, in order to better understand patterns of usage of these products. A questionnaire survey was conducted in Amman (capital). 150 questionnaires were correctly filled then analyzed. The inclusion criteria were Jordanian residents age over18 years and the willingness to participate in the study. The study results showed that the Jordanian population in Amman is familiar with the most important information regarding the risks associated with the use of Analgesics and that they aware of their responsibility of checking medical information before sharing and that is a positive sign.